2024
DOI: 10.3847/1538-4357/ad10ae
|View full text |Cite
|
Sign up to set email alerts
|

Star Formation Efficiency in Nearby Galaxies Revealed with a New CO-to-H2 Conversion Factor Prescription

Yu-Hsuan Teng,
I-Da Chiang,
Karin M. Sandstrom
et al.

Abstract: Determining how the galactic environment, especially the high gas densities and complex dynamics in bar-fed galaxy centers, alters the star formation efficiency (SFE) of molecular gas is critical to understanding galaxy evolution. However, these same physical or dynamical effects also alter the emissivity properties of CO, leading to variations in the CO-to-H2 conversion factor (α CO) that impact the assessment of the gas column densities and thus of the SFE. To address such issues, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 93 publications
0
1
0
Order By: Relevance
“…The advantage in this direction is that the physical quantities at the cloud scale are more strongly linked to the fundamental physics of CO emission and dynamics of molecular clouds. For instance, based on the α CO measurements in this work, Teng et al (2024) have reported an α CO dependence with the cloud-scale velocity dispersion, which likely traces CO opacity change. We also refer the readers to Teng et al (2022Teng et al ( , 2023 for more details.…”
Section: General Suggestions For αCo Prescriptionsmentioning
confidence: 61%
“…The advantage in this direction is that the physical quantities at the cloud scale are more strongly linked to the fundamental physics of CO emission and dynamics of molecular clouds. For instance, based on the α CO measurements in this work, Teng et al (2024) have reported an α CO dependence with the cloud-scale velocity dispersion, which likely traces CO opacity change. We also refer the readers to Teng et al (2022Teng et al ( , 2023 for more details.…”
Section: General Suggestions For αCo Prescriptionsmentioning
confidence: 61%
“…Still, local variations in gas properties, including composition, turbulence, and metallicity, significantly influence the CO-to-H 2 conversion factor (Leroy et al 2011;Narayanan et al 2012;Papadopoulos et al 2012;Bolatto et al 2013;Sandstrom et al 2013;Teng et al 2024). Oxygen abundances compatible with solar metallicity were reported for the NGC 7469 SB ring and outer region by Cazzoli et al (2020) and Zamora & Díaz (2023) using optical nebular lines.…”
Section: Tablementioning
confidence: 94%